Sri Lanka : First Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Sri Lanka. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses Sri Lanka's First Review Under the Extended Arrangement Under the Extended Fund Facility (EFF) and Request for Modification of Performance Criterion (PCs). Performance under the program has been largely satisfactory. All end-June quantitative PCs were met, together with all indicative targets for June. The structural benchmarks due in July-September were not met, but the authorities have been making progress toward their completion which is now scheduled for December 2016. In light of the progress so far and the authorities' policy commitments going forward, the IMF staff supports the completion of the First Review under the EFF.